2022
DOI: 10.1371/journal.pgph.0001104
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of influenza in Ghana, 2011 to 2019

Abstract: Influenza virus is an important contributor to acute respiratory illnesses and is estimated to cause up to 650,000 respiratory deaths each year. Ghana recorded influenza viruses as far back as 1918 when the Spanish influenza pandemic led to the death of >100,000 people in a population of 4 million at the time. An outbreak of highly pathogenic avian influenza A(H5N1) among poultry in Ghana in 2007, led to the establishment of virological surveillance for influenza-like illness (ILI) by the Noguchi Memorial I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In Ghana, influenza circulates all year-round with expected multiple peaks during the major (epi-weeks 14–26) and minor (epi-weeks 32–43) raining seasons ( 13 ). Our observation for 2020 was close to the expected characteristic seasonality in Ghana during the minor raining season.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ghana, influenza circulates all year-round with expected multiple peaks during the major (epi-weeks 14–26) and minor (epi-weeks 32–43) raining seasons ( 13 ). Our observation for 2020 was close to the expected characteristic seasonality in Ghana during the minor raining season.…”
Section: Discussionmentioning
confidence: 99%
“…Influenza A (H3) and B Victoria dominated in the 2020 surveillance season. The influenza season in Ghana is driven by varying strains of seasonal influenza viruses ( 13 ). The transition between influenza strains and other respiratory pathogens remains unpredictable ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Ayim-Akonor et al observed a difference in the prevalence of viral RNA-positive swine swabs according to the season, with detection rates 2.5 times higher during the rainy season compared to the dry season in Ghana [ 20 ]. The rainy season also corresponds to the period of increased influenza virus transmission in the Ghanaian population [ 27 ]. Similar observations were made in Kenya, where increased seroprevalence in pigs followed periods of transmission in human population during colder months [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the period of 2011 to 2019, the National Influenza Center (NIC) received and processed a total of 21,747 respiratory samples from Influenza-Like Illness patients, out of which 3,051 (14.0%) were positive for influenza. Children aged 5-14 years who are the school-going age, documented the highest age-specific influenza positivity rate (21%, 702/3376) [10]. Ntiri et al (2016) in a study at SO and NP Districts in Ghana reviewed the records of 2,322 ILI patients tested from 2014 to 2016.…”
Section: Introductionmentioning
confidence: 99%